Leveraging who you know by what you know: Specialization and returns to relational capital - Byun, Heejung; Frake, Justin; Agarwal, Rajshree (Strategic Management Journal, 2018)
Research Summary : This paper investigates the interaction effects of specialization and relational capital on performance. We distinguish between upstream and downstream relational capital and theorize that higher levels of specialization will buffer against decreases in upstream relational capital, because of deeper domain expertise and stronger downstream relational capital. Conversely, higher levels of generalization permit greater gains from increases in upstream relational capital, due to leverage across a more diversified downstream portfolio of activities. We test and find support for these hypotheses in the context of the US lobbying industry. Our study contributes to the strategic human capital literature by isolating the dimension of specialization and relational capital embodied within individuals and providing performance implications of the interactions. Managerial Summary : Both “what you know” and “whom you know” impacts performance. Generalists and specialists are different on the “what you know” dimension. On the “who you know” dimension, we distinguish between upstream (supplier) and downstream (client) relationships. We show that specialists are buffered by deeper downstream relations from performance declines when their powerful upstream connections lose power. Generalists benefit from broader networks when their upstream connections gain power. Thus, when the value of their relationships change, specialists and generalists should each assess when they can reap performance benefits, and when they need to bolster against adversities. For firms, our study suggests hiring the right mix of specialists and generalists is important to reduce risks from relational losses while enjoying the performance benefits from relational gains.